Groupness in Preverbal Infants: Proof of Concept - Bradley, Benjamin Sylvester; Smithson, Michael (Frontiers in Psychology, 2017)
Infant sociability is generally conceived in terms of dyadic capacities and behaviours. Recently, quantitative evidence has been published to support arguments that infants achieve a criterion for groupness: the capacity to interact simultaneously with two others. Such studies equate this capacity with alternating dyadic acts to the two other members of an interacting trio. Here we propose a stricter threefold criterion for infant groupness, of which the crux is whether the social behaviour of an infant at time B is shown to be influenced by what two or more group-members were previously doing at time A. We test the viability of this conceptualisation: (a) through its justification of the novel laboratory procedure of studying infant sociability in infant-peer quartets (rather than dyads); and, (b) in an analysis of a pilot study of gaze-behaviour recorded in 5-minute interactions among two quartets of infants aged 6-9 months. We call this a ‘proof of concept’ because our aim is to show that infants are capable of groupness, when groupness is conceptualised in a supra-dyadic way—not that all infants will manifest it, nor that all conditions will produce it, nor that it is commonplace in infants’ everyday lives. We found that both quartets did achieve the minimum criterion of groupness that we propose: mutual gaze predicting coordinated gaze (where two babies, A & B, are looking at each other, and B is then looked at by C, and sometimes D) more strongly than the reverse. There was an almost complete absence of ‘parallel mutual gaze,’ where the four babies pair off. We conclude that, under specific conditions, preverbal infants can manifest supra-dyadic groupness. Infants’ capacities to exhibit groupness by nine months of age, and the paucity of parallel mutual gaze in our data, run counter to the assumption that infant sociability, when in groups, is always generated by a dyadic program. Our conceptualisation and demonstration of groupness in eight-month-olds thus opens a host of empirical, theoretical, and practical questions about the sociability and care of young babies.